Antidiabetic effect of Melicope glabra (Blume) T.G. Hartley (Rutaceae) in high-fat diet/streptozotocin-induced diabetic rats and its bioactive components - Quek, Alexandra; Tan, Dai Chuan; Lim, Pei Cee; Kassim, Nur Kartinee; Ismail, Amin; Shaari, Khozirah; Mohd Shuib, Siti Nuraisyah (International Society for Nutraceuticals and Functional Foods, 2022)
Melicope glabra (Blume) T.G. Hartley is a plant of Rutaceae family. The present study aimed to evaluate the in vivo hypoglycemic effect of M. glabra leaves extract on diabetic rats and identify its bioactive components. The induc-tion of diabetes in Sprague-Dawley rats was done by a combination of high-fat diet and low-dose streptozotocin injection. The M. glabra extracts and standard sitagliptin were orally administered once daily to the diabetic rats for 28 days. The diabetic rats showed drastic weight loss, hyperglycemia, poor glucose tolerance, hyperlipidemia, and disturbances in the liver and kidney functions. However, oral administration of M. glabra extracts to the dia-betic rats significantly lowered the DPP-4 level and increased glucagon-like peptide-1 (GLP-1) level. Scopoletin, pachypodol, and stigmasterol were revealed as the active DPP-4 and α-amylase inhibitors. This study revealed novel findings which suggest the potential of M. glabra as alternative antidiabetic treatment and source of anti-diabetic agents